The Method of moments in electromagnetics - Gibson, Walton C.
Now Covers Dielectric Materials in Practical Electromagnetic DevicesThe Method of Moments in Electromagnetics, Second Edition explains the solution of electromagnetic integral equations via the method of moments (MOM). While the first edition exclusively focused on integral equations for conducting problems, this edition extends the integral equation framework to treat objects having conducting as well as dielectric parts.New to the Second EditionExpanded treatment of coupled surface integral equations for conducting an.